Implementation of universal umbilical cord pH analysis in Denmark. A national register‐based study - Charlotte B. Andersson; Line Thellesen; Ulrik S. Kesmodel; Jesper P. Petersen; Søren P. Johnsen (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Umbilical cord blood gas analysis provides information about intrapartum hypoxia and is considered an important measure of quality in maternity care. Universal measurement of umbilical cord pH (UC‐pH), as part of umbilical cord blood gas analysis, has been recommended in Denmark since 2009. The recommendation is that UC‐pH is measured from the umbilical cord artery (pHUA) and vein (pHUV). The aim of this study was to evaluate the national implementation of universal measurement of UC‐pH. Material and methods The study consisted of two parts. First, an evaluation of the implementation, that is, the proportion of births with measured UC‐pH since the recommendation was introduced. Second, an evaluation of the cases in which UC‐pH was missing. This analysis only involved births with gestational age ≥35 + 0 weeks. Results In the period 2009 to 2018 there were 560 889 singleton, live births with registered gestational age in Denmark. The proportion of births with measured pHUA and pHUV increased from 12.4% in 2009 to 82.8% in 2015 and then declined to 76.9% in 2018 (p < 0.001). When comparing the group with missing pH from one or both vessels to the group with both pHUA and pHUV we found lower occurrence of pregnancy and births complications in the first group, body mass index ≥35 (unadjusted RR: 0.89, 95% CI: 0.85–0.93), pregnancy induced medical conditions (RR: 0.86, 95% CI: 0.84–0.89), fetal distress during birth (RR: 0.77, 95% CI: 0.76–0.79), emergency cesarean section (RR: 0.80, 95% CI: 0.78–0.83) and serious births events (RR: 0.80, 95% CI: 0.74–0.86). In contrast, the occurrence of placental insufficiency (RR: 1.07, 95% CI: 1.03–1.11), small for gestational age (RR: 1.36, 95% CI: 1.30–1.43, for <2.3th percentile), hypothermia treatment (RR: 1.60, 95% CI: 1.21–2.14) and neonatal death (RR: 1.96, 95% CI: 1.40–2.74) were higher in the group without measured pHUA and pHUV. Conclusions The use of UC‐pH measurement has increased markedly in Denmark since universal measurement was recommended in 2009. Missing UC‐pH from one or both vessels was associated with less complicated pregnancies and with small for gestational age, hypothermia treatment and neonatal death.